Connecting networked devices prototyping and scaling IoT in the enterprise - Allan, Alasdair; Jepson, Brian 1967- (O'Reilly Media, 2016)
There is no shortage of tutorials for writing your first IoT application, but there's no end of confusion around how to get on a path to production after you have duct-taped a Raspberry Pi to your product. This "one to thousands to millions problem" raises questions of what product to use for going to market, and what to use to connect it to everything else. In this report, you'll learn strategies for scaling up your product and connecting it to the network, while keeping the following constraints front-and-center: Time-to-market requirements Investment you are able to make in non-recurring engineering costs How many products you will sell Physical environment the product must operate in Power requirements All of these affect what options you have available for connecting a networked device, and determine how you will exercise those options
Includes bibliographical references. - Online resource; title from title page (Safari, viewed December 12, 2018)
Keywords: Information technology -- Management; Internet of things; Computer networks -- Management; Technologie de l'information; Gestion; Internet des objets; Réseaux d'ordinateurs; Gestion; Computer networks; Management; Information technology; Management